Structural, optical, electrical and photocatalytic properties Ce-doped SnO2 nanoparticles for photoelectrochemical applications - Hamid Khan; Muhammad Noman Khan; Matiullah Khan; Yaseen Iqbal; Syed Muhammad Ahsan; Hafeez Ullah (Journal of Materials Science: Materials in Engineering, 2025)
Abstract SnO2 nanoparticles accompanied by various concentrations of Ce as dopant material were prepared to extend the optical absorption spectrum near the visible spectrum. The Ce-doped SnO2 NPs at 0.5% (w/w) exhibit significantly higher photocatalytic ability compared to pure SnO2. This enhancement has potential applications in environmental remediation, energy storage, and optoelectronic devices. The microstructures and optical properties of the prepared samples were characterized by XRD, FTIR, EDS, SEM, and UV–vis DRS. The results showed that the nanoparticles are in the tetragonal rutile SnO2 phase. Increasing Ce concentration (over 0.5% (w/w)) shifted the absorption edge towards higher wavelengths and the band gap energy drops from 3.620 to 3.031 eV. The FTIR spectrum confirmed the O–Sn–O bond information in the synthesized samples. The SEM images showed the formation of nearly spherical nanoparticles. Ce-doped SnO2 NPs have smaller primary particles than SnO2 NPs. Reduction in the band gap due to an increase in defects by Ce doping is found and confirmed by the UV–Vis spectra. The existence of Sn and O elements was confirmed by the observed EDS spectra. A plausible photocatalytic mechanism was proposed for the degradation of Methylene blue under UV light to examine the photocatalytic activity of SnO2 and Ce-doped SnO2 NPs photocatalyst. The Ce-doped SnO2 NPs display improved photocatalytic activity compared to SnO2. The influence of Ce concentration doping on the electrical properties was observed at room temperature. Impedance decreases with the frequency and Ce concentration while ac conductivity is increases with the frequency and Ce concentration. The dielectric constant and the dielectric loss rise up with the Ce doping and decrease with the frequency. Among the synthesized samples, the Ce-doped SnO2 depict improved ability of photodegradation and the optimal ability of SnO2 nanoparticles was achieved at 0.5% Ce doping.